(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
One of the most difficult areas of purulent surgery is the development of surgical infection of soft tissues against the background of diabetes mellitus, when necrotic changes dominate. To speed up the process of cleansing and subsequent healing of soft tissue wounds in patients with diabetes, antibacterial drugs, proteolytic enzymes, and ointment dressings are used, depending on the stage of the wound process using physical methods. In this regard, the purpose of this study is to study the antibacterial and anti-inflammatory effect of the drug FarGALS in necrotic soft tissue infections associated with diabetes mellitus. The study was carried out on 103 patients with purulent-inflammatory diseases who were hospitalized at the Republican Center for Purulent Surgery and Surgical Complications of Diabetes Mellitus.